Life satisfaction and longitudinal changes in physical activity, diabetes and obesity among patients with cardiovascular diseases - Michèle Baumann; Anastase Tchicaya; Nathalie Lorentz; Etienne Le Bihan (BMC, 2017)
Abstract Background Patients with cardiovascular disease who underwent coronary angiography at the National Institute of Cardiac Surgery and Cardiological Intervention (INCCI) in Luxembourg were surveyed for cardiovascular risk factors (CVRF) (hypertension, hypercholesterolemia, diabetes, obesity, physical inactivity, tobacco consumption). In 2013/14, their life satisfaction (LS) was also assessed. Our aim was to analyse the relationships between LS on one hand and longitudinal changes in CVRF between 2008/09 and 2013/14 and socioeconomic factors on the other. Methods 1289 patients completed a self-administered questionnaire. Life Satisfaction, originally recorded on a 1 to 10 scale of complete satisfaction was dichotomized into two groups: ≤ 7 and. >7. We then performed logistic multiple regressions. The event on which the probability was modelled, was LS > 7. Data were adjusted on age, sex and income. Longitudinal changes in CVRF were assessed by their presence or absence in 2008/09 and 2013/14 (categories: 'no-no'; 'no-yes'; 'yes-no'; 'yes-yes'). Results Physical activity in 2008/09 and 2013/14 was associated with a lower LS (OR = 0.469). The same pattern was observed for obesity and physical inactivity: lower LS was related to the presence of these risks (yes-yes; no-yes) in 2013/14 (mean OR for obesity and physical inactivity in 2013/14: 0.587 and 0.485 respectively), whereas their presence or absence in 2008/09 was not related to LS. Finally, patients who suffered from diabetes in 2008 were more likely to experience a decline in LS, particularly if their diabetes was less severe in 2013/14 (OR = 0.462). Conclusions The lowest LS was observed when obesity or physical inactivity was present in 2013/14, newly or otherwise. The same trend was seen in diabetes among patients who had it in 2008/9, but were less severely affected in 2013/14. In secondary prevention, CVD-related upheavals could be minimised if professionals and patients became 'Partners in Healthcare' to better adhere to healthy lifestyles, as well as to reduce CVRF, and thereby enhance LS.